Associations among Intimate Partner Violence, Posttraumatic Stress Disorder Symptoms, and Disordered Eating among Women Intimate Partner Violence Survivors Residing in Shelter - Holmes, Samantha C. (Journal of interpersonal violence, 2023)
Previous research has not assessed the association between intimate partner violence (IPV) and disordered eating (DE), nor the potential indirect effect through posttraumatic stress disorder (PTSD) symptoms, among residents of IPV shelters. Among 212 IPV survivors, this study examined these and the differential associations by PTSD symptom cluster and types of DE. In the current sample, 67.9% met criteria for probable PTSD, 20.3% met criteria for a probable eating disorder, and 18.4% had probable comorbid diagnoses. Consistent with escape theory, there was an indirect effect of IPV on DE through PTSD symptoms. Additionally, there was an indirect effect of IPV on weight/shape concerns and binge symptoms through PTSD symptoms. Although there was a significant total effect of IPV on compensatory behaviors, there was no indirect effect through PTSD symptoms. When PTSD symptom clusters were examined concurrently, the only indirect effect of IPV on weight/shape concerns was via the PTSD symptom cluster of negative alterations in cognition and mood. Although there was an indirect effect of IPV on binge symptoms via PTSD symptoms overall, no specific PTSD symptom cluster drove this association. Implications highlight the need for attention to DE within this population. Consistent with escape theory, survivors’ DE might serve to distract from psychological distress.